« Vieille et nouvelle politique » : l’impossible relève générationnelle - Paul Aubert (Mélanges de la Casa de Velázquez, 2006)
In Spain, each new intellectual generation has been driven by a sentiment of rebellion and frustration. This breakdown of inter-generational solidarity has manifested itself successively in different forms of public intervention: struggle for rights, protest, participation in political life or desire to make the revolution. Looking beyond the reciprocal accusations, of the younger generation’s lack of initiative and the elder’s defection, we seek to inquire into the consequences of such a succession of generations without masters or pupils – for the crisis brought on by the conviction of young intellectuals that their actions were part of a process of perpetual renewal meant that for them the present was an impossible dilemma in which they could not develop their ideas. It would thus be a long time yet before Spain succeeded in combining the ideal of modernity with a genuinely contemporary political praxis.